O uso de modelos e aparelhos no ensino de astronomia nas séries iniciais do ensino básico: instrumentos de mediação para o aprendizado - Alcione da Anunciacao Caetano Lobao Veras (2007)
The thematic that this research intended to investigate inserts in the context of the work developed with children from a classroom of the initial series in activity of Natural Sciences Education from the Project Astronomy. This research has for episthemologic premise the perspective that the social interaction in specific institutional spaces is the responsible axis for the knowledge construction process. The individual becomes subject of the learning in the interaction process with the culture and interlocution with the other, which according to Vygotsky, (1986), it integrates the social and the activity. The social one, in this perspective, constitutes the source of the child's conceptual development and it characterizes the organization of the common activity and the students' learning. With Project Astronomy's development it was aimed to contribute for the analysis and reflection on the use of mediation resources as models and devices in the construction of the physical knowledge in the school. The orientation for the pedagogic work in this research context an the school atmosphere tried to provide the effective use of such resources on the part of the children, in constructed situations so that their presence became necessary for the nature of the established interactions between children and the object of the knowledge. The necessity of use and construction of the mediations was a fundamental resource for the rescue of the phenomena, by means of Questioning strategies, investigation and reflection. The research project consisted of producing, with the teacher and researchers participation, interventions that allowed to identify and to evaluate the fulfilled functions and the impacts for fortune produced by the use of the mediation resources in the development and the children's learning. The interventions in the school had occurred during the school year of 2005